Impact of COVID-19 on the oral health of adults in Wuhan and China: results of a nationwide online cross-sectional questionnaire survey - Shuang Zhang (BMC Oral Health, 2021)
Abstract Background COVID-19 has seriously threatened the health and lives of people. This study aimed to investigate the impact of COVID-19 on the oral health of adults in Wuhan and other places of China amid the epidemic and to evaluate attitudes towards dental care in the post-epidemic period. Methods An online cross-sectional survey based on a questionnaire of 22 questions was conducted. Results A total of 3352 valid questionnaires were collected. Participants from Wuhan tended to be relatively psychologically affected and more concerned about future dental treatment. Toothbrushing frequency did not differ significantly between participants from Wuhan and other places and was associated with the prevalence of oral problems people encountered. Gingival bleeding, bad breath and oral ulcers were the three most common oral problems amid the epidemic, and significantly more participants in Wuhan experienced oral problems than other places in China. Conclusion The three most common oral problems amid the epidemic were gingival bleeding, bad breath and oral ulcers. Adults in Wuhan tended to be more seriously affected and suffered more oral problems than people from other places in China. Maintaining good oral health behaviours plays an important role in preventing dental problems. It is crucial to establish and to follow the standard guidelines for the provision of dental care during and after the epidemic.